2019
DOI: 10.3847/2041-8213/ab32ee
|View full text |Cite
|
Sign up to set email alerts
|

Active Asteroid (6478) Gault: A Blue Q-type Surface below the Dust?

Abstract: We present near-infrared spectroscopy of the sporadically active asteroid (6478) Gault collected on the 3 m NASA/Infrared Telescope Facility observatory in late 2019 March/early April. Long-exposure imaging with the 0.5 m NEEMO T05 telescope and previously published data simultaneously monitored the asteroid activity, providing context for our measurements. We confirm Gault is a silicate-rich (Qor S-type) object likely linked to the (25) Phocaea collisional family. The asteroid exhibits substantial spectral va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 36 publications
7
21
0
Order By: Relevance
“…After using the M4AST online tool, Gault can also be associated with Q-type asteroids (figure 5b). This taxonomic classification is consistent with the results from near-infrared spectra exhibiting deep absorption bands near 1 and 2 μm consistent with an S-or Q-type surface composition (Marsset et al 2019;Sanchez et al 2019) and from our visible photometric measurements (see sub-subsection 3.2.1). It is noteworthy that the other two possibilities (B-and C-class) have been reported by Lee (2019b) and Jewitt et al (2019), the spectrum in short wavelengths is very noisy (figure 5), and the chi-square values in table 1 for those three classes are very close to each other if we take the errors into account.…”
Section: Spectroscopic Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…After using the M4AST online tool, Gault can also be associated with Q-type asteroids (figure 5b). This taxonomic classification is consistent with the results from near-infrared spectra exhibiting deep absorption bands near 1 and 2 μm consistent with an S-or Q-type surface composition (Marsset et al 2019;Sanchez et al 2019) and from our visible photometric measurements (see sub-subsection 3.2.1). It is noteworthy that the other two possibilities (B-and C-class) have been reported by Lee (2019b) and Jewitt et al (2019), the spectrum in short wavelengths is very noisy (figure 5), and the chi-square values in table 1 for those three classes are very close to each other if we take the errors into account.…”
Section: Spectroscopic Resultssupporting
confidence: 91%
“…Gault is closer to S-complex. A silicate-rich object (S-or Q-type) is consistent with the result from the near-infrared spectrum (Marsset et al 2019;Sanchez et al 2019) and makes Gault a slight relative of the 25 Phocaea collisional family. Kleyna et al (2019) had an extensive series of observations but they found no convincing lightcurve, meaning the rotational period could only be estimated at ∼1 hr for one peak, and ∼2 hr for two peaks.…”
Section: Spectral Class and Colorssupporting
confidence: 80%
See 2 more Smart Citations
“…where ρ is the density of the ellipsoid and G is the Newtonian gravitational constant. Gault should have a density of roughly equal to 2.2 g cm −3 (Marsset et al 2019;Sanchez et al 2019), consistent with other S-type asteroids (Carry 2012). Figure 10 presents the critical period with which Gault would start shedding surface material as a function of the axial ratio and density.…”
Section: Discussion and Summarysupporting
confidence: 65%